Storage and Transportation of Copper Currency in Late 18th to Early 19th Century: Evidence from Vyatka Province - E. Yu. Mokerova; K. N. Tarasov (Научный диалог)
This study examines the circulation of copper coins in Russia during the late 18th and early 19th centuries, focusing on the Vyatka Governorate. It specifically addresses the storage and transportation of copper currency both within and beyond the region. The research is based on materials from the Central State Archive of Kirov Oblast, including records from the sessions of the Vyatka Treasury Chamber, documents related to the construction and repair of storage facilities for currency in district towns, reports from the Treasury Chamber, contracts with merchants and peasants for the delivery of copper coins, and accounts of vessels transporting copper currency to the capital. The study investigates plans for constructing specialized storage facilities in district towns for copper currency. It has been established that throughout the examined period, despite attempts by the Vyatka Treasury Chamber to find solutions, existing issues concerning the storage of significant quantities of copper coins remained unresolved. The research indicates that transporting copper currency (amounting to several dozen, and at times hundreds, of tons) beyond the Vyatka Province involved addressing a complex set of challenges by the Vyatka Treasury Chamber, including contract negotiations, vessel construction, crew assembly, and security provisions. The findings conclude that the Vyatka Treasury Chamber demonstrated adaptability in responding to emerging difficulties, which effectively minimized disruptions in government contracts for delivering currency to designated locations.